Tingkat Pengetahuan dan Motivasi Ibu Berhubungan dengan Pemberian ASI Eksklusif pada Ibu Bekerja - Tri Utami Listyaningrum; Venny Vidayanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
One of the most problem related to successful exclusive breastfeeding is returning to work after maternity leave. Work and other factors might influence exclusive breastfeeding. It is still found that working mothers do not breastfeed even though their family and their working environment support them. This research is to find out the correlations between mother’s level of knowledge, mother’s motivation and the exclusive breastfeeding among working mothers in PT. Globalindo Intimates Klaten. This research was a quantitative one with a descriptive analytic design. A total sampling method was used to collect the data from as many as 37 working mothers having six-month-old to two-year-old babies. The data were collected in May 2015. The result is indicate that there was a positive correlation between mother’s knowledge of exclusive breastfeeding and the practice of exclusive breastfeeding. The Fisher’s Exact Test with the confidence level of 95% and α 0.05 data analysis indicate that the p-value is 0.022. The result also indicate that indicate that there was a positive correlation between mother’s motivation and exclusive breastfeeding with p-value of 0.003. Conclussion, there was a positive correlation between mother’s knowledge of exclusive breastfeeding and mother’s motivation with practice of exclusive breastfeeding among working mothers in PT. Globalindo Intimates Klaten.